Practical financial management - Lasher, William R. (South Western College Pub., 2000)
This text offers clear, concise, and practical real world treatment of financial management with the assumption that students have little prior knowledge of financial concepts. Written by a former CFO, this book includes cross-functional coverage of the agendas and biases decision makers across the firm may bring to a financial proposal. Advanced math is eliminated from the theory sections and everyday math is geared towards the ability of the typical business student. Numerous worked-out examples and graphical and intuitive presentations support quantitative material.